If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6x + 5 + -7x + 8 = 0 Reorder the terms: 5 + 8 + 3x + -6x + -7x = 0 Combine like terms: 5 + 8 = 13 13 + 3x + -6x + -7x = 0 Combine like terms: 3x + -6x = -3x 13 + -3x + -7x = 0 Combine like terms: -3x + -7x = -10x 13 + -10x = 0 Solving 13 + -10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -10x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -10x = 0 + -13 -10x = 0 + -13 Combine like terms: 0 + -13 = -13 -10x = -13 Divide each side by '-10'. x = 1.3 Simplifying x = 1.3
| Cw+w-cm-m=0 | | r-43=-33 | | v^2-15v+54=0 | | -2p+5p-9=3(p-4)-5 | | (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) | | 8w-21=11 | | -3(-4-6y)+7(-y-5y)=-8 | | 4(1x+9)=56 | | 10(12-5)= | | -m+68=10 | | -3(-4-6y)+7(-y-5w)=-8 | | 10+8q=11+7q | | 85=10-2.5(c) | | 28=5x-2x+4 | | (5x^2-3x+7x)+(4x^2+2x^2+7x)= |